Підготовка вчителя до роботи з обдарованими учнями в Болгарії - Бочарова, Олена (Studies in Comparative Education, 2014)
Зарубіжні дослідження з порівняльної педагогіки свідчать про те, що в шкільних системах різних країн форми роботи та підтримки обдарованих учнів є аналогічними. Відмінності стосуються культурних особливостей країни, домінуючої освітньої ідеології, освітніх традицій, можливостей фінансування роботи з обдарованими дітьми, професійних компетенцій та мотивації вчителів. У статті розглянуто особливості підготовки вчителів до роботи з обдарованими учнями в Болгарії. Автор зазначає, що в країні відбувається цільова підготовка майбутніх учителів у Східно-Західному університеті імені Неофіта Рильського (м. Благоєвград) за авторською навчальною програмою проф. Д. Тодоріної. Представлена авторська модель складається з двох модулів: теоретичного та практичного. Особливу увагу дослідниця концентрує на формуванні у студентів, майбутніх учителів, умінь проводити правильну діагностику. Зарубежные исследования по сравнительной педагогике свидетельствуют о том, что в школьных системах различных стран формы работы и поддержки одаренных учеников являются аналогичными. Различия касаются культурных особенностей страны, образовательной идеологии, возможностей финансирования работы с одаренными детьми, образовательных традиций, профессиональных компетенций и мотивации учителей. В статье рассмотрены особенности подготовки учителей к работе с одаренными учениками в Болгарии. Автор отмечает, что целевая подготовка студентов будущих учителей осуществляется в Южно-Западном университете имени Неофита Рыльского (г. Благоевград) по авторской учебной программе проф. Д. Тодориной. Представленная авторская Модель состоит из двух модулей: теоретического и практического. Особенное внимание исследовательница концентрирует на формировании у студентов умений проведения правильной диагностики. The aim of this article is to show some selected theoretical and practical problems of working with gifted students in the case of Bulgaria. In the research used content analysis method (scientific publications, documents, statistics, international reports) and observation and interview. This article shows changes in the field of identification and support development of gifted pupils. In the article the features of training teachers to the work with gifted students in Bulgaria are examined. The author points out that in East-West University named after Neophytos Rylskiy (Blagoevgrad) it is practised training future teachers according prof. D. Todorina’s curriculum. The presented author’s model consists of two modules: theoretical and practical ones. Particular consideration is given to the formation of future teachers’ diagnostic skills and their personal traits as well which are important for fulfilment the role of a teacher, functioning as a moderator and a mediator. The graduates can be experts and consultants for teachers who work with gifted students, social pedagogues and school teachers at all educational levels and in all types of schools. The objective of the article is analysis the issues of the development of human potential from the perspective of selected educational actions. International comparative studies show that, in the school systems of different countries, similar sets of methods, forms of work and care for talented students are used. The differences are the result of cultural dissimilarities, the dominant ideologies of education, educational traditions, capabilities of financing the activities, competencies and motivations of teachers.